2000
DOI: 10.2307/177507
|View full text |Cite
|
Sign up to set email alerts
|

Response of Bog and Fen Plant Communities to Warming and Water-Table Manipulations

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. Large-scale changes in climate may have unexpected effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(127 citation statements)
references
References 30 publications
8
117
2
Order By: Relevance
“…5). Other studies have also described that the differential response of species and life-forms to treatments may cancel out a clear overall response (Harte and Shaw 1995;Weltzin et al 2000). The studied shrubland was a carbon sink throughout almost all the studied years.…”
Section: Discussionmentioning
confidence: 77%
“…5). Other studies have also described that the differential response of species and life-forms to treatments may cancel out a clear overall response (Harte and Shaw 1995;Weltzin et al 2000). The studied shrubland was a carbon sink throughout almost all the studied years.…”
Section: Discussionmentioning
confidence: 77%
“…Peat accumulation can be claimed as responsible for the decline of Carex species, particularly on the relatively drier hand of the water-tale gradient (Table II). Accordingly, a rapid decline in sedge frequency has been reported after peatland drainage (Laine et al, 1995) or water-table manipulation in mesocosm experiments (Weltzin et al, 2000(Weltzin et al, , 2003. Anyway, the strong decrease of C. rostrata and C. limosa frequencies in the wettest end of the watertable gradient can not be explained by peat accumulation alone.…”
Section: Vascular Plant Dynamicsmentioning
confidence: 92%
“…A second possible explanation stems from the significant correlation between Carex shoot density in 1992 and subsequent frequency decrease (Pearson's correlation = −0.80; P < 0.05), indicating a densityrelated factor. In this case, experimental manipulations have shown that Carex dynamic is negatively affected by litter deposition ("thatch" effect) after some years of increased biomass production, the latter enhanced by high precipitation amounts (Thormann and Bayley, 1997a, b;Weltzin et al, 2000Weltzin et al, , 2003. Indeed, when accumulation of litter reaches critical levels for reducing light penetration and/or peat temperature, sedge biomass decreases.…”
Section: Vascular Plant Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Roots grow faster at higher temperatures in annual crop plants (Kasper & Bland, 1992) and perennials (Larson, 1970 ;Wilcox & Ganmore-Neumann, 1975 ;Teskey & Hinkley, 1981 ;Bevington & Castle, 1985 ;Kuhns et al, 1985 ;Lieffers & Rothwell, 1986 ;McMichael & Burke, 1998 ;King et al, 1999 ;Weltzin et al, 2000). Many of these observations have come from controlled growth-chamber and glasshouse studies, but field experiments and observational studies report similar results.…”
Section:  mentioning
confidence: 97%